Navigating The Implications for Heirs: An Analysis of The Amendment to The Small Estate Act (Distribution) 1955 - Norhazlina Ibrahim; Muhammad Naqiyuddin Ismail; Safeza Mohd Sapian; Asharaf Mohd Ramli; Khairatun Hisan Idris Shazali (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah, Volume 36 Issue 02 Page (118–126)